Modeling of grooved acoustic panels. (May 2017) - Carbajo, J.; Ramis, J.; Godinho, L.; Amado-Mendes, P.
Abstract: Grooved acoustic panels are rigid plates consisting of an interconnected network of periodically arranged slits and circular holes. These devices are traditionally used as resonant absorbers in building acoustics. This paper presents a model to predict the acoustic properties of such absorbers. For this purpose, the classical Johnson-Champoux-Allard (JCA) model and the Transfer Matrix Method (TMM) are used together to describe the acoustic wave propagation through these systems. The proposed model was validated against Finite Element (FE) simulations in terms of sound absorption coefficient under normal incidence, for different configurations with good agreement. Additionally, a parametric study was found very useful to investigate the influence of the geometrical characteristics of the panel on the absorption performance of the absorber and in understanding its acoustic behaviour. As expected, the performance of the absorber varies with the size of the pores and thickness of the panel. The limits of the proposed approach are also discussed. The model is proven to be a useful tool to estimate the acoustic properties of grooved acoustic panel absorbers in a simple manner.